Accurate correction for the matrix interference on laser ablation MC-ICPMS boron isotope measurements in CaCO3 and silicate matrices. Issue 8 (28th June 2021) - Evans, David; Gerdes, Axel; Coenen, Douglas; Marschall, Horst R.; Müller, Wolfgang
Abstract : Refinement of the measurement of the boron isotopic composition of carbonate and silicate materials via LA-ICPMS pushes samples size requirements into the range of SIMS (figure redrawn after Foster et al ., 2018). Abstract : Knowledge of the boron isotopic composition of natural samples has found wide ranging application in both low and high temperature geochemistry. More recently, the development of boron isotope measurements using highly spatially-resolved analytical techniques is of interest as it is increasingly recognised that many materials are heterogeneous with respect to their boron isotopic composition, and moreover, that this heterogeneity yields valuable information about the environment of formation and/or mechanisms of crystallisation. Here, we build on a recently proposed methodology (Standish et al. [2019] Rapid Commun. Mass Spectrom. 33 :959) which enables precise and accurate δ 11 B measurement via LA-MC-ICPMS by accounting for a scattered Ca interference primarily on 10 B. We propose minor modifications to this method via the use of 10 13 Ω preamplifiers on the Faraday cup of the detector, more precise measurement of the Ca interference, and improved modelling of the shape of this interference correction. This yields single laser spot 2SE precision of ∼0.5‰ with a 70 μm beam (∼7 pg B), ∼1.4‰ with a 40 μm beam (∼2 pg B), and a long-term (1.5 year) intermediate precision in a marble standard with 15 μg g −1 [B] of <0.9‰ (2SD). Thus, spatially-resolved information comparable to that achievable via SIMS is possible. Moreover, we show theoretically and empirically that the inaccuracy predominantly resulting from a scattered Ca interference on 10 B is also an issue for non-CaCO3 matrices, despite their typically lower [Ca]. Encouragingly, building multi-standard calibration lines to correct for this interference is also a way forward for silicate glasses, and we demonstrate accurate and precise (<0.5‰ 2SE) measurement of a basaltic glass with 3 μg g −1 [B] using a 74 μm diameter laser beam (<1 pg B). This paves the way forward for accurate and precise spatially-resolved δ 11 B measurement of a diverse range of sample matrices using laser ablation as a sample introduction system for MC-ICPMS instruments that are characterised by a scattered Ca interference in the region of m / z 10–11.